The Leadership and Performance of Nurses in The Hospital - Zamroni, Asroful Hulam; Nursalam, Nursalam; Wahyudi, Andri Setiya (Universitas Airlangga, 2021)
Introduction: the performance of nurses is closely related to organizations and individuals who greatly influence the quality of health services in hospitals. Therefore, improving the performance of nurses through leadership needs to be considered. The study aimed to analyze the relationship between leadership with the performance of nurses in hospital.Method: the design of the study was descriptive correlational with a cross-sectional approach. The sample size of 205 respondents who were selected through simple random sampling technique. The inclusion criteria for respondents were nurse who were implementing nurse, working more than one year, and providing nursing care. The independent variable was the leadership, and the dependent variable was the performance of nurses. The instruments used were the situational leadership questionnaire questionnaire for leadership and the observation sheet: nursing documentation questionnaire for performance of nurse's questionnaire. The data analysed using descriptive analysis and logistic regression test with a significance value of p â‰¤ 0.05.Results: the results showed that the leadership was significantly related to the performance of nurses in hospitals (p = 0.000). The most influential leadership is the democratic leadership. The democratic leadership is mostly owned by nurses with good performance.Conclusion: the leadership of the head of the room with a democratic style can improve the performance of nurses in hospitals by respecting their nature and abilities, encouraging staff to develop, and involving staff in decision making. So that health services in the hospital will be optimal.